SPIRITUALITAS ṢALAWAT WAḤÎDIYYAH DALAM MEMBENTUK KELUARGA SAKÎNAH: KAJIAN PADA JAMA'AH PSW DI REJOAGUNG NGORO JOMBANG - Mas Umar (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2023)
This article examines the Penyiar Shalawat Wahidiyah (PSW) congregation in Rejoagung, Ngoro Jombang. The purpose of this study is to find out how Salawat Wahidiyah can create and have an effect on the sakȋnah family lives of its congregation. Shalawat Wahidiyah is a series of prayers that are structured around the Prophet's shalawat in general, including the procedures and ethics for its practice. This study includes a field study using a sociological-philosophical approach to the mystical paradigm. The methods and implications of the sakȋnah family will be examined using sociological analysis. The research results show that there are five teachings that must be applied in everyday life, namely lillâh-billâh, li al-rasȗl-bi al-rasȗl, li al-ghauts-bi al-ghauts, yukti kulla dzȋ haqq haqqahu, and taqdȋm al-ahamm fa al-ahamm tsumma al-anfa’ fa al-anfa’. This teaching is practical guidance both externally and internally which covers all aspects, both relationships with Allah, His Messenger, and relationships between human beings in society. Congregants practicing Shalawat Wahidiyah who are active in Rejoagung, Ngoro, Jombang show that they feel better in their households, feeling more calm, peaceful and harmonious (sakȋnah).